PENILAIAN CAPABILITY LEVEL DAN MATURITY LEVEL TATA KELOLA TI PADA PT. ABC DENGAN MENGGUNAKAN KERANGKA KERJA COBIT 2019 - Hidayah, Nur Aeni; Normaliza Firdia; Balqis Aulia Rahma; Hafidh Azizah; Diva Amanda (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2025)
To support business strategies and maintain competitiveness, effective information technology (IT) management is very important. This research uses the COBIT 2019 framework to evaluate the capability level and maturity level of IT governance at PT ABC branch. The evaluation focuses on three main domains, namely APO03 (Managed Enterprise Architecture), APO10 (Managed Vendors), MEA03 (Managed Compliance with External Requirements). Data collection was conducted through interviews, observations, and questionnaires with qualitative and quantitative and quantitative approaches. The results of the analysis show that there are deficiencies in IT governance that require improvement with a strategic approach. The recommendations given aim to increase invasion, operational efficiency, and company competitiveness. This research is expected to be a guide for more optimal IT management.